The Effect of Raw Material Inventory Control Costs and Direct Labor Costs on Production Volume (Case Study on Al-Yafi embroidery mukena in Tasikmalaya Regency 2018-2021 Period) - Rismayanti Rismayanti; Suci Putri Lestari; Kusuma Agdhi Rahwana (Penerbit Jurnal Indonesia, 2022)
This study aims to determine and analyze the relationship between the variable costs of controlling the inventory of raw materials and direct labor costs to the volume of production. The research method used is quantitative method and the data used is secondary data obtained directly through interviews with company owners. In this study, sampling used a periodic data approach with a monthly scale of 48 months. What is studied by the author consists of two independent variables and one dependent variable, so the most appropriate analysis tool is multiple linear regression. Based on the results of multiple linear analysis, it is known that the cost of controlling the inventory of raw materials and direct labor costs has a significant effect on the volume of production. It can also be seen from the company's data that every increase in the cost of controlling the inventory of raw materials and direct labor costs, the volume of production also increases. The calculation results show that there is a very strong relationship between the variable costs of controlling raw material inventory and direct labor costs in increasing production volume.